2023
DOI: 10.1039/d2fd00166g
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic reduction of dinitrogen to ammonia using molybdenum porphyrin complexes

Abstract: Porphyrin complexes are well-known in O2 and CO2 reduction, but their application to N2 reduction has not yet been reported. Here, we show that oxo and nitrido complexes of molybdenum...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…83,84 Molybdenum-based materials and molecular complexes have been studied extensively due to its presence in nitrogenases. 85,86 Our very recent theoretical work on Mo + N 2 and Mo − + N 2 reactions disclosed that Mo can transfer five or six electrons to N 2 cleaving its bond and forming either N 2− Mo(V)N 3− or N 3− Mo(VI)N 3− . 11 However, the energy of NMoN is higher than that of the Mo(N 2 ) encounter complex (N 2 weakly interacting with Mo).…”
Section: Resultsmentioning
confidence: 99%
“…83,84 Molybdenum-based materials and molecular complexes have been studied extensively due to its presence in nitrogenases. 85,86 Our very recent theoretical work on Mo + N 2 and Mo − + N 2 reactions disclosed that Mo can transfer five or six electrons to N 2 cleaving its bond and forming either N 2− Mo(V)N 3− or N 3− Mo(VI)N 3− . 11 However, the energy of NMoN is higher than that of the Mo(N 2 ) encounter complex (N 2 weakly interacting with Mo).…”
Section: Resultsmentioning
confidence: 99%
“…An added advantage is the reducing nature of the porphyrin ligand, which has been highlighted in the study by Hegg et al wherein the porphyrin ligands induce the reduction of N 2 to NH 3 . It is also important to note that the metal center in the metalloporphyrin MOFs also serves as a single-atom catalyst (SAC) as the four nitrogen atoms in the porphyrin network form a highly stable M–N 4 complex, thereby avoiding metal aggregation or migration. , The single-atom nature of the Fe center in metalloporphyrin MOFs has been affirmed from the work by Zhang et al when PCN-222­(Fe) MOF comprised of (iron­(III)­meso-tetra­(4-carboxyphenyl)­porphyrin chloride) and H 2 -TCPP (tetra­(4-carboxyphenyl)­porphyrin) showed an excellent electrocatalytic NRR yield of 1.56 × 10 –11 mol cm –2 s –1 with a Faradaic efficiency (FE) of 4.51% at −0.05 V vs reversible hydrogen electrode (RHE).…”
Section: Introductionmentioning
confidence: 99%
“…[5] Among the transition metal complexes, molybdenum complexes have been revealed to work as effective catalysts for ammonia formation under ambient reaction conditions. [5d, [6][7][8] In 2019, we found that the ammonia formation proceeded quite rapidly from the reaction of dinitrogen with samarium diiodide (SmI 2 ) as a reductant and water (H 2 O) as a proton source in the presence of a catalytic amount of a molybdenum(III) trichloride complex bearing pyridine-based PNP-type pincer ligand ([MoCl 3 (PNP)]: 1 a) (Scheme 1a). The proposed reaction pathway of the catalytic ammonia formation using 1 a as a catalyst is shown in Scheme 1b.…”
Section: Introductionmentioning
confidence: 99%